2015
DOI: 10.3758/s13414-015-0989-z
|View full text |Cite
|
Sign up to set email alerts
|

Attentional flexibility and memory capacity in conductors and pianists

Abstract: Individuals with high working memory (WM) capacity also tend to have better selective and divided attention. Although both capacities are essential for skilled performance in many areas, evidence for potential training and expertise effects is scarce. We investigated the attentional flexibility of musical conductors by comparing them to equivalently trained pianists. Conductors must focus their attention both on individual instruments and on larger sections of different instruments. We studied students and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…When junior-and senior-level music education majors played piano while simultaneously listening to an ensemble, their error detection ability decreased (Napoles, Babb, Bowers, Hankle, & Zrust, 2016). In addition, conductors have shown superior divided attention ability compared to pianists for timing tasks but not for pitch tasks-and experts to a greater extent than students (Wöllner & Halpern, 2016). This suggests timing elements prevail over pitch elements and lends support to the recent suggestion that pitch elements should be considered independently of timing elements (Nichols, Wöllner, & Halpern, 2018).…”
supporting
confidence: 58%
“…When junior-and senior-level music education majors played piano while simultaneously listening to an ensemble, their error detection ability decreased (Napoles, Babb, Bowers, Hankle, & Zrust, 2016). In addition, conductors have shown superior divided attention ability compared to pianists for timing tasks but not for pitch tasks-and experts to a greater extent than students (Wöllner & Halpern, 2016). This suggests timing elements prevail over pitch elements and lends support to the recent suggestion that pitch elements should be considered independently of timing elements (Nichols, Wöllner, & Halpern, 2018).…”
supporting
confidence: 58%
“…Participants with high WM seem to perform better during divided attention (Colflesh & Conway, 2007) and high musical expertise may come with enhanced WM capacity for auditory material (Schulze, Zysset, Mueller, Friederici, & Koelsch, 2011). However, professional conductors and pianists show no significant differences in terms of WM, yet conductors outperform musicians in musical divided-attention tasks (Wöllner & Halpern, 2016). Furthermore, WM capacity seems to be task- and domain-dependent and does not necessarily generalize to other domains such as visual-spatial WM tasks (Hansen, Wallentin, & Vuust, 2013; Wöllner & Halpern, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of music specifically, Wöllner and Halpern (2016) reported that in general, expertise increases performance when two music-related tasks are performed simultaneously. Compared to undivided attention, musicians and non-musicians alike are detrimentally affected by divided attention, however, musicians tend to rely on perceptual based coping strategies whereas non-musicians rely on selective attention (Bigand, McAdams, & Forêt, 2000).…”
Section: Memory For Melodymentioning
confidence: 99%
“…Keller and Burnham (2005) found similar results in a dual-task paradigm that examined the recognition and reproduction of matched-metrical and mismatched-metrical rhythmic patterns. In a recent study, Wöllner and Halpern (2016) asked expert and novice conductors and pianists to detect pitch and timing deviations of target tones in selective- and divided-attention tasks (focus on one of two melodic streams, and focus on both streams, respectively). They found that in both tasks experts detected more targets than students.…”
Section: Introductionmentioning
confidence: 99%